Utilization of Artificial Intelligence Technology in Assisting House Chores - Sakkiz Nhizam; Muazzem Zyarif; Sarhad Ziyyo Tuhfa (Newinera Publisher, 2021)
AI is accomplished by the combination of a large amount of input, repetitive analysis, and intelligent algorithms. This enables the program to automatically learn from the trends or features found in the results. Artificial intelligence is also being used in a variety of areas, one of which is schooling. It may also be used to assist households with domestic chores. Technology was developed to improve the life of a large number of citizens. Western technology is heavily reliant on computer technology as a result of a scarcity of human capital. That is why they developed a large number of robotic machines. Technology is extremely beneficial in terms of performance, efficacy, and also cost; utilizing technology is significantly less expensive. Any of the most prominent AI developments are reimagining the consumer electronics market, such as the smarthome. AI has enabled the easy control of household appliances.